The application of code of practice for safety, health and environment for bus company at north Malaysia - Abdul Hanan, Suhaila; Abdul Aziz, Mohamad ‘Amirol; Temizi, Nur Farzana; Sipon, Umi Nur Iryani (2015)
The purpose of this study is to investigate the application of the Code of Practice for safety, health and environment (COP SHE) in Mara Liner, Bintong Travel and Tours and Pancaran Matahari Sdn Bhd. Code of Practice can be defined as a guideline for the employer and employee regarding the relevant and effective technique to manage issues related to occupational, safetyand health. The increasing of number bus accident is getting higher from every year.In the case of accident at Genting Highland bus crashed in the year 2013 it is involved 37 people.The causes of the accident because of speeding and brake malfunction.In order to carry out the study, the semi-structured interview were conducted with the three company was analyzed using thematic analysis.The researcher will review their data, makes notes and begin to sort it into categories. The findings suggest the code of practice (COP SHE) should be applied by bus companies to improve safety and reduce accident in the road.